Building blocks of language - Jones, Christopher D. (HTS teologiese studies, 2021)
Articulate language is a form of communication unique to humans. Over time, a spectrum of researchers has proposed various frameworks attempting to explain the evolutionary acquisition of this distinctive human attribute, some deploring the apparent lack of direct evidence elucidating the phenomenon, whilst others have pointed to the contributions of palaeoanthropology, the social brain hypothesis and the fact that even amongst contemporary humans, social group sizes reflect brain size. Theologians have traditionally (largely) ignored evolutionary insights as an explanatory paradigm for the origin of humankind. However, an increasing number are, of late, contributing to a worldview of humanity which accommodates both the epistemological realities of evolutionary biology as well as insights from theology. This includes reviewing and assessing the origins of articulate language and the physiological attributes necessary for its development. It is in this sense that the evolution of language is relevant from a theological perspective. The association between mental capacity and articulate language, already noted by Darwin, is relevant in explaining the larger group sizes found amongst humans, as is the incipient role played by the evolution of laughter in triggering the neuroendocrine system promoting bonding, to the eventual development of articulate language. Our aim is to review a selection of contemporary perspectives on the evolution of language, amongst others, reasons for the ease with which young children acquire language competency, and whether we may be hardwired for language from birth. Further reading is suggested in the footnotes.Contribution: This article is part of a special collection reflecting on the evolutionary building blocks of our past, present and future. It is based on historical thought and contemporary research with regards to the evolutionary emergence of language. It fits well with the intersectional and trans-disciplinary nature of this collection and journal.